Limb ischaemia and below-knee amputation following life-saving patent ductus arteriosus stent in a critically ill infant. (9th September 2014) - Bharmanee, Apinya; Gowda, Srinath; Singh, Harinder R.
Abstract: Limb ischaemia is a rare but catastrophic complication related to cardiac catheterisation. We report an infant weighing 3 kg with unrepaired tricuspid atresia type 1b, small patent ductus arteriosus, and ventricular septal defect presenting with cardiogenic shock owing to progressively reduced pulmonary blood flow from closing ventricular septal defect and patent ductus arteriosus. An emergency palliative ductal stent was successfully placed with marked clinical improvement. However, acute limb ischaemia developed necessitating above-knee amputation, despite medical management and vascular surgery. The cause of limb loss in our patient was catheterisation-related vascular injury causing arterial dissection–arterial thrombosis in the presence of shock and coagulopathy. This report emphasises the complexity in managing limb ischaemia associated with coagulopathy and highlights the importance of early recognition of reduced pulmonary flow in a single ventricle patient. Timely elective placement of a surgical systemic to pulmonary shunt would prevent catastrophic clinical presentation of compromised pulmonary flow and avoid the need for an emergent life-saving intervention and its associated complications.